2019
DOI: 10.1016/j.ajpath.2018.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Astroprincin (FAM171A1, C10orf38)

Abstract: Our group originally found and cloned cDNA for a 98-kDa type 1 transmembrane glycoprotein of unknown function. Because of its abundant expression in astrocytes, it was called the protein astroprincin (APCN). Two thirds of the evolutionarily conserved protein is intracytoplasmic, whereas the extracellular domain carries two N-glycosidic side chains. APCN is physiologically expressed in placental trophoblasts, skeletal and hearth muscle, and kidney and pancreas. Overexpression of APCN (cDNA) in various cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 33 publications
2
16
0
Order By: Relevance
“…16 Studies showed that FAM171A1 can regulate the cell morphology and invasive growth potential of tumor cells by regulating the dynamics of the actin cytoskeleton. 17 The study conducted by Sanawar et al demonstrated that miR590-5p is a target of ERα in ER receptor-positive BRCA. ERα can stimulate the expression of miR590-5p, and subsequently down-regulated that of FAM171A1 in ERα-positive BRCA cells.…”
Section: Discussionmentioning
confidence: 99%
“…16 Studies showed that FAM171A1 can regulate the cell morphology and invasive growth potential of tumor cells by regulating the dynamics of the actin cytoskeleton. 17 The study conducted by Sanawar et al demonstrated that miR590-5p is a target of ERα in ER receptor-positive BRCA. ERα can stimulate the expression of miR590-5p, and subsequently down-regulated that of FAM171A1 in ERα-positive BRCA cells.…”
Section: Discussionmentioning
confidence: 99%
“…APCN is also expressed in some malignancies, such as nodular melanoma and lobular breast cancer [13]. Higher APCN expression was seen in the tumor invasive front than in the intra-tumoral cells [13]. The authors showed that upregulated APCN expression induced an invasive growth pattern, with sprouting of slender-like projections in melanoma cells [13].…”
Section: Introductionmentioning
confidence: 99%
“…Rasila et al [13] recently characterized a novel endogenous protein called astroprincin (APCN, also known as FAM171A1) that is abundant in brain astrocytes. APCN is an evolutionarily conserved 98-kDa transmembrane type I glycoprotein.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations